Pengaruh Citra Destinasi dan Daya Tarik Wisata Terhadap Minat Berkunjung Kembali dengan Kepuasan Pengunjung Sebagai Variabel Intervening pada Wisata Sarwono di Desa Wonosoco Kecamatan Undaan Kabupaten Kudus - Ismawati Ismawati; Kertati Sumekar; Sutono Sutono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of destination image and tourist attractions on revisit intention with visitor satisfaction as an intervening variable. This study uses primary data in the form of questionnaires. The sampling method used purposive sampling and obtained a sample of 120 respondents. Data analysis used in this study is a structural equation model used software AMOS. The results of this study state that destination image and tourist attractions have a positive and significant effect on visitor satisfaction, destination image does not affect revisit intention, tourist attractions do not affect revisit intention, visitor satisfaction has a positive and significant effect on revisit intention. The results of the mediation analysis state that visitor satisfaction is able to mediate the influence of destination image on revisit intention and visitor satisfaction is able to mediate the influence of tourist attractions on revisit intention